The efficacy and safety of first-line anti-seizure medications as substitution therapy for children with drug-resistant epilepsy: a randomized controlled trial protocol - Perdani, Roro Rukmi Windi; Arozal, Wawaimuli; Mangunatmadja, Irawan; Kaswandani, Nastiti; Handryastuti, Setyo; Medise, Bernie Endyarni; Hardi, Harri; Thandavarayan, Rajarajan Amirthalingam; Oswari, Hanifah (Frontiers in Neurology, 2023)
Although many anti-seizure medications (ASMs) are available, treatment failure, known as drug-resistant epilepsy (DRE), still occurs in around 30% of children with epilepsy. Second-line ASMs are usually used as substitution therapy in DRE to control seizures, although international consensus is not available yet. Previous studies focus on comparing the ASMs, whether as add-on or substitution therapy, mainly conducted in newly diagnosed epilepsy. However, the study that investigated first-line ASMs as substitution therapy compared to second-line ones, particularly among DRE children, is still lacking. A randomized controlled trial (RCT) enrolling 102 participants, aged 1–18, at three referral hospitals in Indonesia will be conducted, dividing them into intervention and control groups. The intervention group will be treated with first-line ASMs as the substitution therapy, while the other in the control group will get second-line ASMs. The primary outcome measure is the proportion difference of responders between groups who get first-line and second-line ASMs in 14 weeks of intervention. Clinical trial registration: ClinicalTrials.gov, identifier NCT05697614.